2018
DOI: 10.3389/fimmu.2018.00444
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor α and Regulatory T Cells in Oncoimmunology

Abstract: Tumor necrosis factor α (TNF) is a potent pro-inflammatory cytokine that has deleterious effect in some autoimmune diseases, which led to the use of anti-TNF drugs in some of these diseases. However, some rare patients treated with these drugs paradoxically develop an aggravation of their disease or new onset autoimmunity, revealing an immunosuppressive facet of TNF. A possible mechanism of this observation is the direct and positive effect of TNF on regulatory T cells (Tregs) through its binding to the TNF re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
129
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(136 citation statements)
references
References 159 publications
(153 reference statements)
6
129
1
Order By: Relevance
“…TNF‐α, a pleiotropic mediator, is central to host defense and inflammatory responses by binding its receptors (TNFR1 and TNFR2) . Initially, TNF‐α was considered as a proinflammatory cytokine.…”
Section: Phenotypic Markers Of M2bmentioning
confidence: 99%
See 4 more Smart Citations
“…TNF‐α, a pleiotropic mediator, is central to host defense and inflammatory responses by binding its receptors (TNFR1 and TNFR2) . Initially, TNF‐α was considered as a proinflammatory cytokine.…”
Section: Phenotypic Markers Of M2bmentioning
confidence: 99%
“…Initially, TNF‐α was considered as a proinflammatory cytokine. However, later preclinical and clinical studies have shown that it also mediates a paradoxical anti‐inflammatory and immune‐modulatory effect . Its pleiotropic effects often lead to opposing outcomes during the development of immune‐mediated diseases .…”
Section: Phenotypic Markers Of M2bmentioning
confidence: 99%
See 3 more Smart Citations